Effect of the Outer Layer of Al Coatings Deposited by Cold Gas Spray on the Microstructure, Mechanical Properties and Corrosion Resistance of the AA 7075-T6 Aluminum Alloy - da Silva, F. S. [UNESP]; Cinca, N.; Dosta, S.; Cano, I. G.; Guilemany, J. M.; Benedetti, A. V. [UNESP] (Springer Nature, 2020)
The corrosion of AA 7075-T6 aluminum alloy is a critical issue for many industries. In this study, aluminum coatings were deposited onto AA 7075-T6 by cold gas spray and the effect of the porous outer layer on different properties of the coating, including corrosion–resistance was investigated. As-prepared and polished samples were used to study the microstructure, morphology, mechanical properties and corrosion resistance of the coating in 3.5 wt.% NaCl solution. Cross-sectional analysis showed a dense structure, low porosity (0.8%) and thickness up to 300 µm (~ 100 µm for the porous outer layer and ~ 200 µm for the compact inner layer). The sliding wear test resulted in a volume loss of 3.2 × 10−4 mm3/Nm with an adhesive wear mechanism. The abrasive wear test showed a wear rate of 1.1 × 10−4 mm3/Nm for the as-prepared coating and 0.8 × 10−4 mm3/Nm for the polished coating. The as-prepared coating pores and interparticle spacing in the outer layer were mostly responsible for the increase in wear rate. For the polished coating immersed in 3.5 wt.% NaCl solution during 900 h, the electrolyte reached some specific points of the substrate as revealed by the cross-sectional analysis. Inspection of the as-prepared coating demonstrated that the coating/substrate interface was completely damaged after long immersion times (~ 900 h).
Keywords: AA 7075-T6; aluminum; cold spray; corrosion; metal coatings; Thermal spray; wear